2023
DOI: 10.35848/1347-4065/acae62
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of conductive elastomeric composites for directly printed intrinsically stretchable conductors

Abstract: Intrinsically stretchable solid-state conductors can shed light on the realization of further biocompatible and reliable wearable electronics. However, their material composition should be optimized considering the compatibility of target stretchable platforms. In this paper, we report directly printable conductive elastomeric composites for intrinsically stretchable conductors. Pneumatic direct ink writing (DIW) system is employed to deposit well-defined patterns. Polydimethylsiloxane (PDMS), Ag particles, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…19,30,31 In this regard, the automated 3D printing process emerges as a powerful solution, enabling the customization of TE arrays with high resolution tailored to the shape and structure of the applications. 32,33 This customization can be achieved using rheology-modulated materials, which range widely from inorganic substances to polymers. 34−36 Most notably, the 3D printing process can facilely fabricate 3Dstructured TE modules in an additive manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,30,31 In this regard, the automated 3D printing process emerges as a powerful solution, enabling the customization of TE arrays with high resolution tailored to the shape and structure of the applications. 32,33 This customization can be achieved using rheology-modulated materials, which range widely from inorganic substances to polymers. 34−36 Most notably, the 3D printing process can facilely fabricate 3Dstructured TE modules in an additive manner.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have reported strategies to modify device designs, such as introducing wavy or origami structures to overcome the associated limitations of planar-type modules and highly integrated TE arrays. These modifications, however, often require additional post-structural deformation processes. ,, In this regard, the automated 3D printing process emerges as a powerful solution, enabling the customization of TE arrays with high resolution tailored to the shape and structure of the applications. , This customization can be achieved using rheology-modulated materials, which range widely from inorganic substances to polymers. Most notably, the 3D printing process can facilely fabricate 3D-structured TE modules in an additive manner. This capability is crucial for developing temperature sensors capable of imposing temperature gradients in the out-of-plane direction when placed on target surfaces, thereby enhancing the detection of temperature changes.…”
Section: Introductionmentioning
confidence: 99%